2014
DOI: 10.1038/srep05216
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of intracellular and cell membrane redox systems in Saccharomyces cerevisiae

Abstract: Redox mediators can interact with eukaryote cells at a number of different cell locations. While cell membrane redox centres are easily accessible, the redox centres of catabolism are situated within the cytoplasm and mitochondria and can be difficult to access. We have systematically investigated the interaction of thirteen commonly used lipophilic and hydrophilic mediators with the yeast Saccharomyces cerevisiae. A double mediator system is used in which ferricyanide is the final electron acceptor (the repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 46 publications
(60 reference statements)
0
65
0
Order By: Relevance
“…Conversely, BESs aim to electrochemically intercede with microbial metabolism for the production of various compounds of interest1516. Electronic interrogation of biological systems with redox molecules has allowed for detection of changes in cell metabolic activity171819, redox state202122, toxicity23 and other parameters4. Cells have been engineered for enhanced electron flow2425 and to allow for electronic detection of engineered cell activity2627.…”
mentioning
confidence: 99%
“…Conversely, BESs aim to electrochemically intercede with microbial metabolism for the production of various compounds of interest1516. Electronic interrogation of biological systems with redox molecules has allowed for detection of changes in cell metabolic activity171819, redox state202122, toxicity23 and other parameters4. Cells have been engineered for enhanced electron flow2425 and to allow for electronic detection of engineered cell activity2627.…”
mentioning
confidence: 99%
“…Recently, mediated electrochemical methods have been used for several potential applications, such as biotoxicity assessment, biochemical oxygen demand assay, and even for the controlled release property of β-cyclodextrin [9][10][11][12][13][14][15][16][17][18]28]. This method is characterized by high levels of microorganisms and mediator in order to facilitate the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…4 curves b and c show that the steady-state voltammograms of ferrocyanide accumulations obtained after 2 h incubation of the bacterium with glucose and ferricyanide (or DCPIP-ferricyanide system) mixture have shifted up the current axis and there is both anodic current (arising from oxidation of ferrocyanide) and cathodic current (arising from reduction of ferricyanide). The steady-state anodic plateau current measured at E = 500 mV was used as a relative measure of the amount of ferrocyanide produced, which is related to the physiological status of the bacteria [15]. The controlled experiment has also been performed in the absence of cells and confirmed that the reduction of ferricyanide does not happen if only the monosaccharide glucose and ferricyanide are present in the incubation solutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations